Unbroken [videorecording (DVD)] - Lane, Beth (Greenwich Entertainment, 2025)
UnBroken chronicles the seven Weber siblings who evaded certain capture and death and ultimately escaped Nazi Germany following their mother's incarceration and murder at Auschwitz. After being hidden in a laundry hut by a benevolent farmer, the children spent two years on their own in war torn Germany. Emboldened by their father's mandate that they 'always stay together,' the children used their own cunning and instincts to fight through hunger, loneliness, rape, bombings and fear. Their journey culminates with a painful ultimatum, when, separated from their father, they are told that they must declare themselves as orphans to escape to a new life in America. Unbeknownst to them, this salvation would become what would finally tear them apart, not to be reunited for another 40 years.